2001
DOI: 10.1002/job.128
|View full text |Cite
|
Sign up to set email alerts
|

The social construction of fairness: social influence and sense making in organizations

Abstract: SummaryThis paper explores how the social relationships employees have with peers and managers are associated with perceptions of organizational justice. These relationships are theoretically modelled as the conduits for social comparison, social cues, and social identi®cation, which are sources of sense making about fairness`in the eyes of the beholder.' It is argued that perceptions of procedural and interactional justice are affected by this type of social information processing because: (1) uncertainty exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 58 publications
3
114
0
5
Order By: Relevance
“…Most of the research on vicarious justice experiences has not been conducted in organisational settings -examples are tests of the deontic theory of fairness (Folger 2001), research on the just world hypothesis (Lerner 1980), or research on the persistent injustice effect (Davidson and Friedman 1998). Yet first contributions in organisational contexts also indicate that the justice experiences and the justice judgments of one's peers do matter (Colquitt et al 2002;Lamertz 2002). For example, research showed that a person's reaction could be strongly influenced by social reports of others having received similar treatment survey and laboratory studies, support a main effect for others' procedural justice on one's own feelings and actions.…”
Section: Justice In Teamsmentioning
confidence: 99%
“…Most of the research on vicarious justice experiences has not been conducted in organisational settings -examples are tests of the deontic theory of fairness (Folger 2001), research on the just world hypothesis (Lerner 1980), or research on the persistent injustice effect (Davidson and Friedman 1998). Yet first contributions in organisational contexts also indicate that the justice experiences and the justice judgments of one's peers do matter (Colquitt et al 2002;Lamertz 2002). For example, research showed that a person's reaction could be strongly influenced by social reports of others having received similar treatment survey and laboratory studies, support a main effect for others' procedural justice on one's own feelings and actions.…”
Section: Justice In Teamsmentioning
confidence: 99%
“…These findings support Lamertz (2002), Colquitt (2004), and Umphress et al (2003), and Boivie et al (2015) demonstrating that perceptions of justice of individuals are influenced by their relationships with the managers and other peers in their organisations, by investing how these relationships could affect equity judgement of land-acquired households and recognising that relationships is one of the most important moderators of equity judgement.…”
Section: Social Relationshipssupporting
confidence: 71%
“…Social relationships (Colquitt, 2004;Lamertz, 2002;Umphress, Labianca, Brass, Kass, & Scholten, 2003) and culture (Kilbourne & O'Leary-Kelly, 1994;T.-Y. Kim & Leung, 2007;Leung & Stephan, 1998) are the social moderators that have influences on perceptions of equity.…”
Section: Moderators Of Equity Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, independente do número de dimensões consideradas, as organizações atualmente estão preocupadas com o modo como seus empregados experimentam a justiça, não só no que se refere às recompensas que eles recebem da relação de emprego, mas também do modo como são tratados pelo sistema organizacional e por seus agentes (Lamertz, 2002). Essa preocupação, em parte, deve-se ao fato de que a literatura vem demonstrando que níveis mais elevados de percepções de justiça estão, de forma geral, associados a comportamentos mais positivos no local de trabalho (Rahim, Magner & Shapiro, 2000).…”
Section: Introductionunclassified